Graikų karų su persais recepcija romėniškoje Graikijoje: Herodotas Plutarcho akimis - Juchnevičienė, Nijolė (Literatūra, 2015)
The traditional image of Sparta in the European cultural tradition is an idealized distortion of reality, based on the works of non-Spartan writers in both Greek and Roman antiquity. Plutarch has influenced our image of Sparta more than any other author, though he was not the first to create the so-called Spartan mirage. Plutarch idealized Sparta, according to him the ideal of a polis community was best of all realized in the Sparta of Lycurgus. It is the ethics of the rulers, not the type of the political system, that really matters for him; the moral standards of the rulers determine the moral value of the state. The example of the Spartan ethics to the last degree has been demonstrated, according Plutarch, in the battle at Thermopylae. Plutarch regards this battle as the most important moment of the Greco-Persian wars; in his eyes it brought the final victory to Greeks at the end. Therefore he is extremely harsh in criticizing Herodotus for his description of this epizode (De malignitate Herodoti). Plutarch’s attitude towards Herodotus in this work and in Lives, which owe material to Herodotus, is extremely different. According to Plutarch, Herodotus had a personal dislike for Sparta and therefore he had blackened the greatest deed of Leonidas. Herodotus and Plutarch look at this epizode from the different points of view. Herodotus is not influenced by later Spartan ideology here. Though his narrative of Thermopylae is infused with Homeric elements, he presents it not simply as an act of heroism, but as the deepest personal tragedy of Leonidas and the 300 Spartiatai; there is a colour of ambivalence in his story. Therefore Plutarch relies more on Ephorus/Diodorus than on Herodotus reconstructing his version of events and widely uses the rhetorical and moralistic approach, elaborated already by the authors mentioned. It is the rhetorics of Plutarch and his predecessors that underlies the ideological cliché of nowadays political rhetorics.